Actualización del sistema de revisión de precios del mercado enfocado a remodelaciones de obras del Banco Nacional - Hernández-Pereira, Bryan (Instituto Tecnológico de Costa Rica, 2016)
In collaboration with the Price revision system of The National Bank, a study of construction market as well as the adjustment of its budgeting tool in order to improve its administrative contractive processes. To achieve the objectives, the remodeling of the National Bank is characterized in its different branches. The processes of price revision system are identified, and the necessary requirements for the processes are recognized. In addition, an improvement proposal to the database is done. The information was obtained from interviews that were held with a selection of functionaries of the bank. Prices of materials and rental equipment providers were requested during the interviews. The reasons that originate the remodeling of the bank and the architectural details were determinated. There is a description of the origin, purpose, process, and the methods for the price revision. Inputs for setting unit costs were obtained in remodeling activities and new unit costs were added. The remodeling satisfies the needs of the bank, but a price revision by means of a high quality budgeting tool will be needed in order to contribute to the choice of a company that will run the remodeling processes.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Presupuesto; Precios; Calidad